Explanation of women's reproductive health rights in PIK-R group Talagening Village, Purbalingga Regenc - Riani, Evicenna Naftuchah; Pangesti, Wilis Dwi; Kartini, Ika Ariani (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2024)
The high number of cases of violence against women and children must be a common concern. Women and children are very vulnerable to violence, therefore all parties must make a joint movement to prevent all acts of violence.Women must be literate or aware of their reproductive health rights in order to avoid various types of violence. The types of violence experienced by female victims, both adults and children, are physical, psychological, sexual, neglect, trafficking, exploitation and others.This service focuses oncounseling on women's reproductive health rights as a preventive effort so that people are able to be literate/aware of women's reproductive health rights.The number of women in Purbalingga Regency over the age of 18 who became victims of violence in 2019 was 23 cases, in 2020 there were 17 cases and in 2021 there were 3 cases. Meanwhile, the number of girls aged 0-18 years who experienced violence in 2016 was 31 cases, in 2017 there were 18 cases and in 2018 there were 23 cases.This service activity focuses on educating women's reproductive health rights as an effort to increase public knowledge, especially women so that they are able to improve women's health and lives.The method used is lecture, discussion and question and answer.Participantactively participate in discussions and ask questions about things that are not understood. The discussion process discussed issues related to women's reproductive health rights.The result of the activity is that there is an increase in knowledge about women's reproductive health rights.